Cost-Effectiveness of Pembrolizumab Regimens for the First-Line Treatment of Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma in Argentina - Wurcel, Victoria (Adv Ther, 2021)
INTRODUCTION: The phase III KEYNOTE-048 trial showed that the programmed death receptor 1 (PD-1) inhibitor pembrolizumab, in the combined positive score (CPS) ≥ 1 population and combined with platinum + 5-fluorouracil in the total population, improves survival over cetuximab + platinum + 5-fluorouracil in recurrent or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). We evaluated the cost-effectiveness of pembrolizumab as monotherapy in the CPS ≥ 1 population or combined with platinum + 5-fluorouracil in the total population versus cetuximab + platinum + 5-fluorouracil from the social security perspective in Argentina. METHODS: A partitioned survival model projected costs and outcomes over 20 years with 3% annual discounting. Health state occupancy was modeled using KEYNOTE-048 Kaplan–Meier curves until the final analysis data cutoff, followed by parametric extrapolations guided by statistical criteria. Costs for initial and subsequent treatments, disease and adverse events management, and terminal care were included (AR $74.00 = 1 USD). Time-on-treatment and EuroQol five-dimension scores were taken from KEYNOTE-048. Utilities were derived using an Argentina-specific algorithm. RESULTS: With pembrolizumab monotherapy, patients accrued 1.1040 additional life-years and 0.8768 additional quality-adjusted life-years (QALYs), for incremental cost-effectiveness ratios (ICERs) of AR $135,801/life-year and AR $170,985/QALY gained over cetuximab + platinum + 5-fluorouracil. Additional life-years and QALYs gained with pembrolizumab combination therapy versus cetuximab + platinum + 5-fluorouracil were 1.3296 and 1.0536, respectively (ICERs of AR $680,143/life-year and AR $858,306/QALY). Considering a threshold of AR $1,676,122/QALY gained, pembrolizumab monotherapy and combination therapy had an 88.0% and a 77.1% probability of being cost-effective, respectively. CONCLUSION: Pembrolizumab either as monotherapy or in combination with chemotherapy offers substantial survival gains for patients with R/M HNSCC at small additional costs, making it a cost-effective treatment versus cetuximab + platinum + 5-FU in Argentina.